2019
DOI: 10.1186/s13024-019-0309-5
|View full text |Cite
|
Sign up to set email alerts
|

Sleep oscillation-specific associations with Alzheimer’s disease CSF biomarkers: novel roles for sleep spindles and tau

Abstract: Background Based on associations between sleep spindles, cognition, and sleep-dependent memory processing, here we evaluated potential relationships between levels of CSF Aβ 42 , P-tau, and T-tau with sleep spindle density and other biophysical properties of sleep spindles in a sample of cognitively normal elderly individuals. Methods One-night in-lab nocturnal polysomnography (NPSG) and morning to early afternoon CSF collection were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 78 publications
7
47
1
Order By: Relevance
“…In human studies, sleep spindle density and duration, but not SWA, are negatively associated with CSF-measured total and hyperphosphorylated tau levels in cognitively asymptomatic older adults (Kam et al, 2019). A similar finding was observed with slow wave-sleep spindle coupling strength, over frontal and parietal derivations, in relation to MTL tau burden in cognitively asymptomatic older adults (Figures 1B,D) (Winer et al, 2019).…”
Section: Tau Pathology and Local Sleep (T)supporting
confidence: 60%
“…In human studies, sleep spindle density and duration, but not SWA, are negatively associated with CSF-measured total and hyperphosphorylated tau levels in cognitively asymptomatic older adults (Kam et al, 2019). A similar finding was observed with slow wave-sleep spindle coupling strength, over frontal and parietal derivations, in relation to MTL tau burden in cognitively asymptomatic older adults (Figures 1B,D) (Winer et al, 2019).…”
Section: Tau Pathology and Local Sleep (T)supporting
confidence: 60%
“…It has been suggested, however, that by taking advantage of the high intra-individual night-to-night consistency it would be possible to use spindles to track progression of neurodegeneration longitudinally (Clawson et al, 2016;Seibt et al, 2016). Spindle density has been reported to change during aging (Purcell et al, 2017) as well as during neurodegenerative diseases such as Parkinson's disease (Emser et al, 1988), Alzheimer's disease (Kam et al, 2019), and Huntington's disease (Wiegand et al, 1991). Indeed, there is post hoc evidence to suggest that sleep spindles can be used as early predictors of neurodegenerative disorders (Latreille et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This correlation was especially strong with t-tau as well as with the ratio of t-tau/Aβ. Nevertheless, CSF tau measures did not correlate with total sleep time nor with sleep quality [120]. So, spindle density in N2 could be another candidate as AD biomarker.…”
Section: Other Possible Biomarkersmentioning
confidence: 82%
“…Interestingly, of the three, t-tau was the one that most significantly associated with sleep spindle density, after adjusting for age, sex and ApoE4. Moreover, spindle duration, count, and density of fast spindles also correlated negatively with t-tau levels [120]. Lastly, Holth et al (2019) found that the sleep-wake cycle and sleep deprivation influenced the amount of tau in interstitial fluid and CSF, both in experimental animals and in humans.…”
Section: Sleep and Tau Pathologymentioning
confidence: 97%
See 1 more Smart Citation